Mesopic visual acuity is less crowded - Pluháček, František; Siderov, John (Graefe's archive for clinical and experimental ophthalmology, 2018)
Purpose The decrease in visual acuity under low luminance conditions is well known. Recent laboratory evidence showed that crowding under low luminance (mesopic) light levels is less robust than under photopic conditions. The present study examines whether such differences in crowding influence clinical measurements of mesopic visual acuity, including test-retest repeatability. Methods Twenty adult subjects with normal or corrected to normal visual acuity were recruited for the study. Monocular visual acuity was measured under photopic (228 cd/m 2 ) and mesopic (0.164 cd/m 2 ) luminance conditions using a letter chart, similar in principle to the ETDRS logMAR chart, presented on a computer monitor. Three rows of five letters, each row differing in size by 0.05 logMAR from largest to smallest were displayed at the center of the monitor. The level of crowding was varied by varying the separation between horizontally adjacent letters from 100% optotype size to 50, 20, and 10% optotype size. Inter-row spacing was proportional to optotype size. Observers read the letters on the middle row only. Measurements continued by reducing the size of the letters, until three or more errors on the middle row were made. Each correctly identified letter contributed 0.01 to the recorded logMAR score. All measurements were repeated for each subject on two separate days. Results Visual acuity (logMAR) was significantly better under photopic than mesopic luminance conditions with a mean difference of 0.48 logMAR. Visual acuity also decreased with decreasing letter separation (i.e. increase in crowding). However, the decrease in visual acuity for the smallest letter separation was less under the mesopic luminance condition, even after accounting for the increased size of threshold acuity letters. Test-retest repeatability for mesopic and photopic conditions was not significantly different. Conclusions Crowding under mesopic luminance conditions has less impact on visual acuity than under photopic luminance.